Penggunaan Metode Cash Flow Monitoring Pada Sistem Informasi Pemantauan dan Evaluasi Dana PKK Di Desa Tempel Jaya - Ayulia Indah Utami; Samsudin; Adnan Buyung Nasution (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
The manual management of PKK activity funds in Tempel Jaya Village leads to reporting delays, lack of transparency, and difficulty in real-time cash flow evaluation. This study aims to develop a web-based information system for monitoring and evaluating PKK activity funds using the cash flow monitoring method. The research method used is Research and Development (R&D) with the Prototyping model, including stages of problem identification, data collection, product design, validation, revision, black-box testing, and trial use. The result is a PHP and MySQL-based information system capable of recording income and expenditure transactions, providing a real-time dashboard with cash flow trend graphs, and generating financial reports (cash flow, balance position, transaction recap) in PDF/Excel formats. The application of the cash flow monitoring method successfully calculates net cash flow, closing balance, and fund efficiency ratio based on the 2025 PKK budget data with a total budget of more than Rp142 million. In conclusion, this system improves transparency, accountability, and efficiency of PKK fund management. Future development suggestions include integration with mobile applications and automatic notification features.